Food consumption pattern and food security status of maize farmer households in Galis District, Bangkalan - Setiani, Setiani; Wijayanti, Dian Eswin; Priyanto, Moh. Wahyudi (AGROMIX, 2024)
Introduction: This study examines the food consumption patterns and food security status of corn farming households in Paterongan Village, Galis Subdistrict, Bangkalan Regency, Madura Island, Indonesia. The research is conducted within the context of the low food security levels in Indonesia, despite the implementation of the Sustainable Development Goals (SDGs) since 2015. Paterongan Village serves as an interesting case study due to its high corn production but also a high poverty rate, which raises concerns regarding household-level food security. This study aims to identify the factors influencing food security among corn farmers in the area. Methods: This research uses a descriptive quantitative approach, collecting data through interviews and questionnaires with 76 female corn farmers. The 24-hour food recall technique was applied to assess food consumption patterns and calculate the Household Dietary Diversity Score (HDDS). Binary logistic regression analysis was conducted to identify the factors influencing food security. Results: The findings indicate that the food consumption patterns are relatively limited in diversity, with most households primarily consuming cereals, vegetables, oils, legumes, and fish. The average HDDS score is 7.1, with 67% of households classified as food insecure. Conclusion: The logistic regression analysis identified education level, household income, and the utilization of home gardens as significant factors that improve food security.